Efavirenz promotes β-secretase expression and increased Aβ1-40,42 via oxidative stress and reduced microglial phagocytosis: implications for HIV associated neurocognitive disorders (HAND). - Lecia A M Brown; Jingji Jin; Darren Ferrell; Edin Sadic; Demian Obregon; Adam J Smith; Jun Tan; Brian Giunta (PLoS ONE)
Efavirenz (EFV) is among the most commonly used antiretroviral drugs globally, causes neurological symptoms that interfere with adherence and reduce tolerability, and may have central nervous system (CNS) effects that contribute in part to HIV associated neurocognitive disorders (HAND) in patients on combination antiretroviral therapy (cART). Thus we evaluated a commonly used EFV containing regimen: EFV/zidovudine (AZT)/lamivudine (3TC) in murine N2a cells transfected with the human "Swedish" mutant form of amyloid precursor protein (SweAPP N2a cells) to assess for promotion of amyloid-beta (Aβ) production. Treatment with EFV or the EFV containing regimen generated significantly increased soluble amyloid beta (Aβ), and promoted increased β-secretase-1 (BACE-1) expression while 3TC, AZT, or, vehicle control did not significantly alter these endpoints. Further, EFV or the EFV containing regimen promoted significantly more mitochondrial stress in SweAPP N2a cells as compared to 3TC, AZT, or vehicle control. We next tested the EFV containing regimen in Aβ - producing Tg2576 mice combined or singly using clinically relevant doses. EFV or the EFV containing regimen promoted significantly more BACE-1 expression and soluble Aβ generation while 3TC, AZT, or vehicle control did not. Finally, microglial Aβ phagocytosis was significantly reduced by EFV or the EFV containing regimen but not by AZT, 3TC, or vehicle control alone. These data suggest the majority of Aβ promoting effects of this cART regimen are dependent upon EFV as it promotes both increased production, and decreased clearance of Aβ peptide.